CHALLENGES AND OPPORTUNITIES: ASSESSING SMART CITY READINESS IN MAGELANG CITY FOR SUSTAINABLE CHANGE - Orbawati, Eny Boedi; Muhammad, Irsyad (Universitas Padjadjaran, 2024)
This study aims to analyze the extent to which technological infrastructure, digital governance, and community participation can support the implementation of the Smart City concept in Magelang City. The research method used is included in the category of qualitative approaches that describe findings through online media. The data sources for this study are online news media, social media and journals related to the research by exploring the breadth of technological infrastructure and digital governance. The analysis technique uses the NVivo 12 plus data processing application, a computer-aided qualitative document analysis tool. Their tools are easy to use and can process words and explore word frequencies, attributes, and cases from big data. The results of the study show that Magelang City has great potential to become a sustainable smart city through the application of the smart city concept. Infrastructure support and local government commitment are the basis for utilizing technology and innovation to improve the quality of life of its citizens. Focusing on digital connectivity, green energy implementation, city security, and community participation are key strategies. Despite facing challenges in indicators such as smart mobility, smart economy, and smart environment, concrete efforts can be seen through the Smart Magelang Application initiative. The results of the analysis also reflect careful planning in the 2021-2026 RPJMD. Thus, Magelang City has great potential to become an efficient, innovative, and sustainable smart city.